Foley Catheter or Oral Misoprostol for Induction of Labor in Women with Term Premature Rupture of Membranes: A Randomized Multicenter Trial - Kruit, Heidi; Tihtonen, Kati; Raudaskoski, Tytti; Ulander, Veli-Matti; Aitokallio-Tallberg, Ansa; Heikinheimo, Oskari; Paavonen, Jorma; Rahkonen, Leena (American Journal of Perinatology, 2016)
Objectives To compare the Foley catheter and misoprostol for induction of labor in term women with premature rupture of membranes.Study Design A randomized controlled trial was performed in three university hospitals in Finland between March 2012 and September 2014. A total of 202 term women with ruptured membranes >18 hours, singleton pregnancies in cephalic presentation, unfavorable cervix, and no prior cesarean section were enrolled. Participants were randomly allocated to induction of labor by Foley catheter or oral misoprostol in a 1:1 ratio. All women received prophylactic antibiotics. The main outcomes were cesarean section and maternal and neonatal infections.Results Labor induction by Foley catheter or misoprostol showed no difference in cesarean delivery rates (23.6 vs. 18.2%; odds ratio [OR], 1.39; 95% confidence interval [CI], 0.69–2.82; p = 0.36), maternal intrapartum infections (2.2 vs. 2%; OR, 1.12; 95% CI, 0.15–8.9; p = 1.00), postpartum infections (1.1 vs. 2.0%; OR, 0.55; 95% CI, 0.05–6.18; p = 1.00), or neonatal infections (1.1 vs. 5.1%; OR, 0.21; 95% CI, 0.24–1.87; p = 0.22). The total time from induction to delivery was similar (1,311 vs. 1,435 minutes; p = 0.31) in the two groups.Conclusions Foley catheter or misoprostol can both be used for induction of labor in women with term premature rupture of membranes.
Keywords: premature rupture of membranes; induction of labor; Foley catheter; misoprostol